Fungal deterioration of oil cakes during storage - K.I. WILSON, A. NASEEMA and (Indian Phytopathology, 2002)
Twenty two fungi were isolated from oil cakes of coconut, groundnut and sesame, collected from different oil mills during 3 different periods of the year. Of these, Aspergillus flavus and A. niger were isolated from all the samples of groundnut and sesame oil cakes, and from 88.89% and 77.78% of coconut oil cakes, respectively. Penicillium pinophilum was also isolated from all the 3 oil cakes under study. Oil cakes collected during June-July had the highest population of fungi. There was a positive and significant correlation between weather parameters and the population of fungi.